To Study Female Prefers of Purchasing Lipstick from Nykaa and Sugar in Ahmedabad City - Ghevariya, Dikshita; Prajapati, Leha; Vidani, Jignesh (MultiTech Publisher, 2024)
This study investigates the preferences of female consumers in Ahmedabad regarding lipstick purchases from Nykaa and Sugar, with a focus on the role of age in shaping purchasing decisions. Using a quantitative approach, the research tested multiple hypotheses to explore the relationships between age and various factors such as frequency of purchase, brand perception, pricing, packaging, and promotional influences. The findings reveal that age significantly impacts perceptions of product quality, value for money, pricing, and satisfaction with brand offerings, but these relationships tend to be weak. For instance, younger consumers were found to be more responsive to promotional offers and pricing, while older consumers prioritized product quality and brand trust. Interestingly, no significant association was found between age and preferences for online versus in-store purchases, suggesting that e-commerce strategies should be tailored to offer a seamless omnichannel experience. The study also found that satisfaction with both Nykaa and Sugar was influenced by factors such as packaging appeal, the color range of lipsticks, and brand loyalty. The research provides valuable insights for brands looking to target different age groups by tailoring their marketing strategies, product offerings, and customer engagement efforts. Furthermore, it highlights the importance of personalized approaches in a competitive beauty industry, especially considering the shifting dynamics of consumer preferences in urban areas